Evolution of Schooling Behavior in Threespine Sticklebacks Is Shaped by the Eda Gene. Issue 2 (1st June 2016) - Greenwood, Anna K; Mills, Margaret G; Wark, Abigail R; Archambeault, Sophie L; Peichel, Catherine L
Abstract: Despite longstanding interest in the genetic mechanisms that underlie behavioral evolution, very few genes that underlie naturally occurring variation in behavior between individuals or species are known, particularly in vertebrates. Here, we build on our previous forward genetic mapping experiments and use transgenic approaches to identify Ectodysplasin as a gene that causes differences in schooling behavior between wild populations of threespine stickleback ( Gasterosteus aculeatus ) fish. This work provides rare insight into the proximate mechanisms that have shaped the evolution of vertebrate behavior.